Socio-economic importance and study of the ecological, morphological, genetic and biochemical variability of Baobab (Adansonia Digitata L.) in Benin - Assogbadjo, Achille Ephrem; Sinsin, Brice; Van Damme , Patrick (Afrika Focus, 2006)